Mathematical representation: A bibliometric mapping of the research literature (2013–2022) - Fredi Ganda Putra; Dewi Lengkana; Sugeng Sutiarso; Nurhanurawati Nurhanurawati; Antomi Saregar; Rahma Diani; Santi Widyawati; Suparman Suparman; Khoirunnisa Imama; Rofiqul Umam (Jurnal Infinity, 2024)
Mathematical representation ability is an essential skill for students to understand mathematical concepts. Many studies have been conducted regarding this ability, but it is necessary to map existing research to provide a clearer picture of future research topics. This study aims to provide a bibliometric review of trends using mathematical representation skills in mathematics teaching research. The method in this study is bibliometric analysis, which aims to analyze and classify bibliographic material by presenting representative summaries of the literature in the Scopus database. The search was carried out using the keyword "mathematical representation" and selecting "article title" in the search menu in the Scopus.com database. Perish or Publish (PoP) software analyzes the author's name, number of document citations, document title, year of publication, document source, publisher, and document type. The results showed 99 publications and 357 citations related to mathematical representations, where the number of publications and citations fluctuated. The application of learning models and approaches, computer media, and analysis of mathematical representations is a research trend related to this variable. Therefore, paying attention to mathematical representations in learning mathematics and using effective strategies to improve students' mathematical representation abilities is essential. The findings of this study indicate the need to develop syntax and learning media based on mathematical representations to strengthen students' mathematical abilities.